Financial Analysis of “Corporation Bank” with Special Reference to Trichy, Tamilnadu - Srinivasan, Dr.R. (IJRDO - Journal of Business Management, 2018)
Financial analysis of an organization provides the clear view of its performance parameters, present as well as past performance. This analysis is important for the management and also for outsiders dealing with organization as this shows the way of functioning and the direction in which an organization is moving. It is helpful in assessing the corporate excellence, judging the credit worthiness, processing bond rating and assessing market risk. The main study is to find out the financial performance of the bank. The ratio analysis and interpretation can provide valuable insights into a bank‟s performance.